KARAKTERISASI MOLEKULER DAN UJI PATOGENESITAS STREPTOCOCCUS PATOGEN ISOLAT ASAL BALI - Suarjana, I Gusti Ketut; Asmara, Widya (Buletin Veteriner Udayana, 2012)
The main of this study were characterized of muramidase released protein (MRP) andexctracellular factor (EF) as virulence factor of Streptococcus beta hemolityc of Bali islotesand its patogenecity on mice.The MRP was isolated from the cell walls bacteria withmuramidase (lysozyme) and EF was obtained from supernatant of bacteria precipated with70% ammonium sulphate and then dialysed. These protein were identified by usingsodium-dodecyl sulphate polyacrylamide gel electrophoresis ( SDS-PAGE). Isolates thatwas observed are five consist of three isolates from pigs and two isolates from monkeys.Pathogenecity test using 20 mices divided into four group. Group I inoculated with 0,1 mltodd-hewitt broth steril as negative control, group II inoculated with 0,1 ml inoculum ofbacteria of Streptococcus suis type 2 (strain D282) as positive control, group III inoculatedwith 0,1 ml Streptococcus beta haemolytic isolated from monkey and group IV inoculated with 0,1 ml Streptococcus beta haemolytic isolated from pig. The result of this studyshowed that all isolates were consist of eight protein bands of MRP and one EF of 110 kDamolecular weight. Eight protein MRP were 125 kDa, 76 kDa, 60 kDa, 57 kDa, 48 kDa, 45kDa, 30 kDa, and 28 kDa respectively. Each isolates had two major protein bands of MRP(76 kDa and 45 kDa).The patogenecity test in mice showed that the morbidity andmortality rates were 100% and 60% respectively. The prevalence of meningitis in mice are100%. Clinical sign were observed 30 hour post inoculated (pi) whereas mice found deathstarty 48 pi.
Keywords: Muramidase Released Protein (MRP), Exctracelluler Factor (EF), Streptococcus